The Protective Effects of Sodium Pentaborate Tetrahydrate Against UVB-induced Apoptosis in Human Keratinocytes - ABDİK, EZGİ AVŞAR (Hitit Üniversitesi, 2022)
Ultraviolet radiation (UV) is an environmental carcinogen causing human skin cancer. Exposure of the skin to UV produces apoptotic keratinocytes called sunburn cells within the epidermis. Boron, an essential element for plants, has several biological properties, such as anti-cancer, anti-microbial, and anti-oxidant. In the present study, the possible protective effects of sodium pentaborate tetrahydrate (SPT) against UVB-induced apoptosis in human keratinocyte cells, HaCaT, were investigated. They were treated with SPT at different concentrations (7.8-125 μg/mL) for 24h after UVB irradiation (20, 30 and 60mJ/cm2). Cell viability, annexin V assay, cell cycle analysis, and apoptosis-related gene levels were measured using RT-PCR. Treatment with SPT (15.6-31.25μg/mL) after 30 mJ/m2 UVB exposure significantly increased cell survival. Annexin V apoptosis analysis demonstrated a robust protective effect by treatment with SPT at concentrations of 15.6 and 31.25μg/mL after 30mJ/cm2 UVB irradiation. The cell cycle analysis revealed that UVB irradiation elevated the number of cells at the G0/G1 phase while SPT treatment after UVB irradiation increased the number of cells at G2/M phase, suggesting the changes were partially reversed. Furthermore, treatment with 15.6μg/mL SPT after 30 mJ/m2 UV irradiation blocked the activation of Caspase 3, Caspase 9, Bax, And P53. These results indicate that treatment with SPT exerts protective effects after UVB irradiation. Thus, treatment with SPT led to strong protection against UVB-induced apoptotic cell death in HaCaT cells.
Keywords: Sodium Pentaborate Tetrahydrate; UVB Irradiation; Apoptosis; Keratinocyte